FIRST CASE REPORT OF ANCA-ASSOCIATED VASCULITIS AND ANTHRACOSIS COEXISTENCE - Dogan, Emrah; Kandemir, Ozan; Oral Tapan, Özge; Tapan, Utku; Olcay, Sabri Serhan; Çelik, Özgür İlhan; Mouline Doğan, Marwa (Journal of Ayub Medical College Abbottabad, 2023)
Anthracosis is a type of mild pneumoconiosis secondary to harmless carbon dust deposits. Although anthracosis was previously associated with inhaled coal particles, such as coal workers' pneumoconiosis, this hypothesis was later abandoned; pathology has been associated with inhaled dust particles. Our paper is the first case report of ANCA-associated vasculitis and anthracosis coexistence. In addition, it aims to highlight that histopathologically proven anthracotic granulomatous nodules can show high FDG uptake in PET/CT contrary to expectation. We present a case of a 73-year-old male with p-ANCA-associated vasculitis and anthracotic lung nodules accompanied by radiological and clinical findings. The patient got diagnosis with p-ANCA-associated vasculitis with serological and rheumatological tests. Atypically, the clinical findings of the patient were weak (No dyspnoea, cough or additional pulmonary complaints). Nodules were present on X-ray graphics and nodules' contours were irregular on CT. On PET/CT, SUV values of the nodules were high [12 kBq/mL]. Histopathological specimens showed multiple lung granulomas including anthracosis particles. Until performing the biopsy, we could not exclude the possibility of malignancy. Conclusion: When lung involvement of vasculitis is superimposed by anthracosis, it can create granulomas with high SUV values. The relationship between anthracosis and parenchymal lung diseases is a current topic and many recently published papers are present on this subject. To the best of our knowledge, our paper is the first paper showing the relationship between parenchymal involvement of vasculitis and anthracosis in the literature. Environmental pollution and dust particles are the known reasons for anthracosis particles in the nodules. It is open to future research on whether air pollution triggers new atypical cases or not.